Technetium-99 Conjugated with Methylene Diphosphonate Ameliorates Ovariectomy–induced Osteoporotic Phenotype without Causing Osteonecrosis in the Jaw - Zhao, Yinghua (2012)
Technetium-99 conjugated with methylene diphosphonate ((99)Tc-MDP) is a novel bisphosphonate derivative without radioactivity and has been successfully used to treat arthritis in China for years. Since bisphosphonate therapy has the potential to induce bisphosphonate-associated osteonecrosis of the jaw (BRONJ), we examine whether (99)Tc-MDP represents a new class of bisphosphonate for anti-resorptive therapy to ameliorate estrogen deficiency–induced bone resorption with less risk of causing BRONJ. We showed that (99)Tc-MDP-treated ovariectomized (OVX) mice had significantly improved bone mineral density (BMD) and trabecular bone volume in comparison to the untreated OVX group by inhibiting osteoclasts and enhancing osteogenic differentiation of bone marrow mesenchymal stem cells (BMMSCs). To determine the potential of inducing BRONJ, (99)Tc-MDP/dexamethasone (Dex) or zoledronate/Dex were administered into C57BL/6J mice via the tail vein, followed by extraction of maxillary first molars. Interestingly, (99)Tc-MDP treatment showed less risk to induce osteonecrosis in the maxillary bones compared to zoledronate treatment group, partially because (99)Tc-MDP neither suppressed adaptive regulatory T cells (Tregs) nor activated the inflammatory T-helper-producing interleukin 17 cells (Th17). Taken together, our findings demonstrate that (99)Tc-MDP therapy may be a promising approach in the treatment of osteoporosis with less risk of causing BRONJ.